An integrated approach with vardenafil orodispersible tablet and cognitive behavioral sex therapy for treatment of erectile dysfunction: a randomized controlled pilot study. (September 2015) - Boddi, V.; Castellini, G.; Casale, H.; Rastrelli, G.; Boni, L.; Corona, G.; Maggi, M.
Summary Erectile Dysfunction is considered a multifactorial disease, where organic and psychological aspects are often interconnected. In a randomized controlled pilot study, we compared the efficacy of combined vardenafil orodispersible tablet (VARD) and cognitive‐behavioral sex therapy (CBST) vs. VARD alone in improving sexual symptoms in both male and female partners. Thirty male patients with erectile dysfunction, and their partners were randomly assigned with a 2 : 1 ratio, to two different arms and treated for 10 weeks with VARD (Group A; n = 19) or VARD+CBST (Group B; n = 11). International Index of Erectile Dysfunction (IIEF‐15), Female Sexual Function Index (FSFI) and Index of Sexual Satisfaction (ISS) were, respectively, administered to male, female, and both partners at times (T) 0, 1 (+5 weeks of therapy) and 2 (+10 weeks of therapy). Groups A and B were similar in their sociodemographic and clinical characteristics. Pre‐treatment (T0) test scores did not significantly differ among the groups. In both group A and B, the IIEF‐Erectile Function domain showed a significant improvement from T0 to T1 (p = 0.005 and p < 0.0001 vs. T0, respectively) and from T0 to T2 only in group B (p = 0.013). In group A, FSFI and both male and female ISS did not show any significant change at T1 and T2 vs. T0. In group B, a significant improvement at final time‐point in FSFI and male and female ISS scores was reported (p < 0.05, T2 vs. T0 in all scores). The results of our study suggest that both VARD alone and VARD+CBST improved erectile function, however, only VARD+CBST improved couple sexual satisfaction and female sexual function.